Evaluation of the effectiveness of Hand Hygiene Awareness Raising Campaigns during the Covid-19 pandemic: A review of the latest literature - Zakir, M. (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The Covid-19 pandemic, caused by the SARS-CoV-2 virus, has impacted human health and hygiene worldwide. Maintaining hand hygiene is crucial to halt the spread of the virus. Handwashing and the use of hand sanitizers have been recognized as effective methods to prevent virus transmission. Awareness campaigns on the importance of handwashing have increased alongside the virus's spread. This research is a literature review that integrates data from various sources. Data were collected from national journals and critically analyzed to gain a better understanding of the effectiveness of hand hygiene awareness campaigns during the Covid-19 pandemic in Indonesia. The method employed is descriptive, analyzing data from various sources to present comprehensive information. The research findings indicate that these campaigns have enhanced public knowledge and behavior regarding hand hygiene. Campaigns were carried out through various means such as socialization, teaching, providing handwashing facilities, setting examples, and online campaigns. The objective is to raise public awareness about the importance of regular and proper handwashing to prevent the spread of Covid-19.